Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4sm01249f
|View full text |Cite
|
Sign up to set email alerts
|

Light controlled friction at a liquid crystal polymer coating with switchable patterning

Abstract: We describe a new methodology that enables dynamical control of motion through modulating the friction at coating surfaces by exposing to UV light. The principle is based on reversible switching of the surface topographies of the coating by light. The coating surface transfers from flat in the dark to corrugated in the presence of UV by forming regular ridge-like line gratings. Both the static and the kinetic friction coefficient are investigated in a dynamic manner by switching between the off (flat surface) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…The fingerprint texture is of particular interest as it contains multiple alignment regions (homeotropic and planar) directly upon application, and does not require additional electric fields or other processing states to achieve this condition. By containing both planar and homeotropic alignment regions in the same coating, the film will both expand and compress, respectively, leading to larger deformations [94,101]. For these types of azo-LCN coatings, it was found that the actuation and relaxation time were both close to 10 s [103].…”
Section: Light-induced Reversible Surface Topographies In Azo Cross-lmentioning
confidence: 93%
See 3 more Smart Citations
“…The fingerprint texture is of particular interest as it contains multiple alignment regions (homeotropic and planar) directly upon application, and does not require additional electric fields or other processing states to achieve this condition. By containing both planar and homeotropic alignment regions in the same coating, the film will both expand and compress, respectively, leading to larger deformations [94,101]. For these types of azo-LCN coatings, it was found that the actuation and relaxation time were both close to 10 s [103].…”
Section: Light-induced Reversible Surface Topographies In Azo Cross-lmentioning
confidence: 93%
“…This makes the coating more attractive for applications such as generation of variable friction surfaces that can respond in the order of seconds (see Figure 11d,e). fields creates azo-LCN coatings with alternating domains of planar (director parallel to the substrate) cholesteric and homeotropic (director perpendicular to the substrate) nematic alignment within the same film (see Figure 11a-c) [94,101]. With this alignment setup, the coating will contain areas that expand and contract in thickness adjacent to one another, resulting in larger differential topographical features.…”
Section: Light-induced Reversible Surface Topographies In Azo Cross-lmentioning
confidence: 99%
See 2 more Smart Citations
“…SMP coatings that change both topography and color are appealing for a range of reconfigurable nanophotonic devices for optical data storage, photovoltaics, and optical sensors, as well as smart adhesives, biosurfaces, and battery‐free optical time‐analyte indicators . Regular surface topographies exhibiting structural colors have been fabricated in SMPs by top‐down methods including locally induced surface wrinkling, nanoimprint lithography, compression molding, or templating via microspheres .…”
Section: Introductionmentioning
confidence: 99%